2020
DOI: 10.1080/02687038.2020.1781777
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of time reference in production and comprehension in Thai speakers with agrammatic aphasia

Abstract: Background: It has been demonstrated that reference to the past is difficult for individuals with agrammatic aphasia, leading to the formulation of the PAst DIscourse LInking Hypothesis (PADILIH). Many of the previous studies have focused on Indo-European languages, in which time reference is expressed through verb inflection. The current study examined the PADILIH in Thai, a language that does not use verb inflection but instead uses aspectual markers to refer to time. Aims: We aimed to evaluate the pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A similar finding was mentioned in the investigations of the Thai language in the Literature Review (Siriboonpipattana et al, 2020). Researchers studying Thai aphasics concluded that this phenomenon depends on the language structure, which might be the case for Azerbaijani as well.…”
Section: Morphological Errorssupporting
confidence: 78%
“…A similar finding was mentioned in the investigations of the Thai language in the Literature Review (Siriboonpipattana et al, 2020). Researchers studying Thai aphasics concluded that this phenomenon depends on the language structure, which might be the case for Azerbaijani as well.…”
Section: Morphological Errorssupporting
confidence: 78%
“…Furthermore, only the sentence level was considered in our study. Therefore, it would be interesting to include discursive tasks, such as picture descriptions or interviews, in future studies (Arslan et al, 2016;Siriboonpipattana et al, 2020). Such tasks, which have better ecological validity, could be more cognitively demanding, as they involve message planning, lexical retrieval, and syntactic structure building in addition to verb tense computation.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies (Faroqi-Shah and Thompson, 2007;Bastiaanse et al, 2011) had mixed results depending on the language assessed or the task used. Eleven studies (Wenzlaff and Clahsen, 2004;Nanousi et al, 2006;Kok et al, 2007;Aithal et al, 2009;Miozzo et al, 2010;Fyndanis et al, 2012;Thompson et al, 2013;Patterson and Holland, 2014;Auclair-Ouellet et al, 2019;Fyndanis and Themistocleous, 2019;Siriboonpipattana et al, 2020) did not statistically analyze tenses differences. Therefore, quantitative analysis in the IPD meta-analysis will provide more insight into these results.…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…Another notable study of [22] carried out a time reference analysis in Thai speakers with agrammatic aphasia. The analysis aimed to investigate if referring to the past, present, and future was possible among individuals with agrammatic aphasia.…”
Section: Literature Reviewmentioning
confidence: 99%